Global Analysis of Three-Dimensional Shape Symmetry: Human Skulls (Part II) - Tran, Vi Do; Dao, Tien-Tuan; Nguyen, Tan-Nhu (Journal of Technical Education Science, 2022)
Facial mimics are important to human life, so facial palsy negatively affects the involved patients. Recently, the comparison of muscle action lengths between the left and right-hand sides has been used to evaluate facial palsy quantitatively. However, even in the healthy subjects, their left and right muscle action lengths could not be perfectly symmetrical. These action lengths were formed by insertion points on the head and attachment points on the skull. Consequently, the geometrical dissymmetry between left and right human skulls needs to be analyzed and reported quantitatively. So far, no studies have reported this quantity. In this paper, in the second part of our study, we analyzed symmetrical levels between the left and right sides of human skulls. In particular, 329 skull models reconstructed from computed tomography (CT) images of healthy subjects in neutral mimics were used for calculating. The left and right skull regions were mirrored through a center plane of the skull. Hausdorff distance and volumetric differences between the left skulls (skull convex hulls) and mirrored right skulls (skull convex hulls) were computed as the distance and volumetric symmetries, respectively. As a result, the distance dissymmetrical values (Mean ± SD) are 1.2680 ± 0.3538 mm, and ones of volumetric dissymmetry (Mean ± SD) are 32.1790 ± 23.2725 cm3. In perspective, we will analyze the skull symmetry in more detail with different local shape topologies. Moreover, the global and local shape symmetries will be implemented in our clinical decision support system for facial mimic rehabilitation.